The new world of philanthropy: How changing financial behavior, public policies, and COVID‐19 affect nonprofit fundraising and marketing. Issue 3 (28th June 2022) - Van Steenburg, Eric; Anaza, Nwamaka A.; Ashhar, Ahmed; Barrios, Andres; Deutsch, Ashley R.; Gardner, Meryl P.; Priya, Preeti; Roy, Abhijit; Sivaraman, Anu; Taylor, Kimberly A.
Abstract: Evolving financial behavior, an unpredictable public policy atmosphere, and an unparalleled global pandemic have collaborated to disrupt nonprofit fundraising. The COVID‐19 pandemic alone exacerbated consumer demands for nonprofit services while curtailing nonprofit organizations' ability to fundraise. Without fundraising, nonprofit organizations cannot achieve their mission or support their causes, leading to a precarious situation for societal well‐being. Meanwhile, consumers are changing their financial behaviors, with younger generations often going cashless. At the same time, governments continue to change policies that affect nonprofit organizations. In keeping with the transformative consumer research movement, the present study provides a conceptual framework for the state of nonprofit fundraising amid the challenges associated with changes in financial behavior and public policy, coupled with the effects of the global pandemic. Marketing strategies for fundraising success are presented to aid nonprofits going forward and serve societal interests.